INVENTORY OF THE INVASIVE ALIEN PLANT SPECIES IN INDONESIA - SRI SUDARMIYATI TJITROSOEDIRDJO (SEAMEO BIOTROP, 2005)
An inventory of the alien plant species in Indonesia based on the existing references and herbarium specimens concluded that 1936 alien plant species are found in Indonesia which belong to 187 families. Field studies should be done to get the complete figures of alien plant species in Indonesia. Based on the existing figures of the plant species, the invasive alien plant species can be identified, followed by studies on the assessment of losses, biology, management and their possible utilizations. Alien plant species are imported to Indonesia for cultivation, collection of the botanical garden, as experimental plants or other curiosities. Aside from plants purposely imported, there are also introduced plant propagules contaminating imported agricultural products. These alien plant species can be beneficial or have a potential of being invasive. The alien cultivated species consisted of 67% of the total number. More than half of the cultivated plants are ornamental plants. Some of the species are naturalized or escaped from cultivation and become wild and invasive. Some other naturalized species, adapted well without any problems of invasion. There are 339 species or 17% of the species recorded as weeds. The highest record of weeds is found in the family of Poaceae (57 species), followed by Asteraceae (53 species) and Cyperaceae (35 species). There are 6 families having more than 10 species of weeds: Amaranthaceae, Asteraceae, Cyperaceae, Euphorbiaceae, Poaceae, and Rubiaceae. Three families have more than 100 species: Asteraceae 162 species, Poaceae 120 species, and Papillionaceae 103 species. Five species of aquatic and 20 species of terrestrial plants considered as important alien plant species in Indonesia were identified and some of their distributions noted. Keywords: Alien plant species/Invasive alien plants/Weeds/Environmental weeds/Aquatic and terrestrial alien plants